Short-term isokinetic and isometric strength outcomes after anterior cruciate ligament reconstruction in adolescents. (January 2022) - Weaver, Adam; Ness, Brandon M.; Roman, Dylan P.; Giampetruzzi, Nicholas; Cleland, Joshua A.; Pace, J. Lee; Crepeau, Allison E.
Abstract: Objectives: To examine differences in knee strength outcomes after ACL reconstruction according to quadriceps tendon (QT) or hamstring tendon (HT) autograft in adolescents. Design: Retrospective cohort. Methods: Surgical and clinical outcome data were collected. Analyses were conducted separately for female and male cohorts and grouped by graft type (HT or QT). A Mann-Whitney U test of independent samples was used to examine group differences according to graft type. Results: 107 females (age = 15.6 ± 1.5 years) and 94 males (age = 15.7 ± 1.5 years) were included. Mean time since surgery ranged from 7.2 to 7.9 months. Those with a QT autograft had decreased normalized isokinetic quadriceps peak torque on the involved limb compared to the HT group (p < 0.01, ES = 0.71–0.89). Normalized isometric hamstring peak torque was decreased for those with HT autograft in the female cohort (p = 0.02, ES = 0.57). Conclusion: Normalized isokinetic quadriceps peak torque was reduced by 18–20% on the involved limb in those with a QT autograft. Normalized isometric hamstring peak torque was decreased by 13% for those with HT autograft in the female cohort. Method of strength testing may be an important consideration to fully appreciate strength deficits after ACL reconstruction according to graft type. Highlights: Knee strength outcomes were analyzed according to graft type and sex during late-stage ACLR rehabilitation in adolescents. QT graft groups had reduced normalized isokinetic quadriceps peak torque by 18–20% compared to HT graft groups. There were no difference between groups in isometric quadriceps peak torque in the involved limb for both males and females. Female HT group had a 13% normalized isometric hamstring strength deficit compared to the QT group. There were no differences in patient reported outcomes (Pedi-IKDC) between groups.